Relationship Between Staging and Carcinoembryonic Antigen Serum Levels In Colorectal Cancer Patients' - Agusrly, Chandra; Sungkar, Taufik; Siregar, Gontar Alamsyah (TALENTA Publisher, Universitas Sumatera Utara, 2020)
The staging can be used as one of the prognostic factors providing a clinical picture of the patient in the future in colorectal cancer patient. In addition, carcinoembryonic antigen (CEA) as tumor markers can determine the commonly used diagnosis and prognosis of colorectal cancer. Objective: The aims study was to investigate the relationship of the staging and carcinoembryonic antigen serum levels in colorectal cancer patients. Methods. This was an analytical study with a cross-sectional design. The sample used was colorectal cancer patients at H. Adam Malik General Hospital, Medan from January 2016 to December 2018. As many as 52 subject study who met the inclusion and exclusion criteria. The Kruskal-Wallis test was used to determine relationship between staging and CEA serum levels. Results: The median value of carcinoembryonic antigen levels in Stage I, II, III, and IV group was (2.74 ng/ml vs 6.16 ng/ml vs 2.52 ng/ml, vs 26.87 ng/ml; p=0.003) respectively. Conclusion: There was relationship between staging and carcinoembryonic antigen serum levels in colorectal cancer patient